Der militärische Arm der Europäischen Union - Carchedi, Guglielmo (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2006)
This essay examines whether the European Union, already the most powerful economic and financial rival of the United States, can develop its military arm to a level compatible with its economic and financial weight. It concludes by suggesting a parallel between European currency and the European military. The ECU started as virtual money that evolved into the Euro to become a real danger for the U.S. dollar. At this point, the nascent EU army is only a potential threat to a still unchallenged U.S. military power, but a parallel and ominous evolution is under way.